2016
DOI: 10.1111/tri.12754
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas transplantation in older patients is safe, but patient selection is paramount

Abstract: SUMMARYPancreas transplant outcomes have progressively improved. Despite this, some centers have continued to employ historical age limits for pancreas transplant candidates. We sought to determine the importance of chronological age in determining patient and graft survival rates after pancreas transplantation. A single-center, retrospective study of adult, deceased donor simultaneous pancreas and kidney (SPK) and solitary pancreas transplants (SP, including pancreas transplant alone and pancreas after kidney… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 25 publications
3
48
1
2
Order By: Relevance
“…Scalea et al . analysed 720 recipients of whom 28 were over 55 years and found that older recipients receiving SPK had better survival than those receiving kidney alone. While there may be some evidence that the excellent glycaemic control achieved in SPK transplantation may have some survival benefit, it must be recognized that in this analysis, the recipients selected for SPK and those selected for kidney alone had different comorbidity profiles resulting in selection bias and therefore making the groups incomparable.…”
Section: Discussionmentioning
confidence: 99%
“…Scalea et al . analysed 720 recipients of whom 28 were over 55 years and found that older recipients receiving SPK had better survival than those receiving kidney alone. While there may be some evidence that the excellent glycaemic control achieved in SPK transplantation may have some survival benefit, it must be recognized that in this analysis, the recipients selected for SPK and those selected for kidney alone had different comorbidity profiles resulting in selection bias and therefore making the groups incomparable.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary disease is a significant concern before and after pancreas transplantation [10,17,18]. Perhaps resulting from decreased surgical volumes, the true frequency of CAD amongst recipients of pancreas transplants is understudied.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps resulting from decreased surgical volumes, the true frequency of CAD amongst recipients of pancreas transplants is understudied. Knowledge of the burden of CAD in the modern era is particularly important as patients are getting older before they are referred for transplantation [5,10]. Recognizing increasing volumes at our center in the setting of an aging and increasingly co-morbid pancreas transplant population, we sought to determine how many of our pancreas transplant recipients were affected by CAD [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Further, receiving a simultaneous pancreas kidney (SPK) transplant improves life expectancy over kidney transplantation alone. 4,5 Despite this, the total number of pancreas transplants in the United States has decreased since 2006.…”
Section: Improvement In Pancreas Transplant Evaluation and Surgical Vmentioning
confidence: 99%